Through a Critical Realist Lens: Investigating Data Collection and Analysis Techniques in a Qualitative Study About Internet-Related Child Protection Risks for Children and Young People with Disabilities - Flynn, Susan; Byrne, Julie (My University, 2025)
This paper applies a critical realist philosophical position to collect and analyse data from 34 children and young people with disabilities about the child protection and welfare issues associated with internet use. This study utilised a blend of methods for data collection and a defined data analysis frame which is presented in this paper. This data analysis frame offers learning about how qualitative findings can be applied to critical realism, explaining the position of causal mechanisms within the digital realities of children and young people with disabilities. The purpose of this paper is to add to emerging critical realist methodological literature by delineating the data collection processes involved in doing research with children and young people with disabilities and by providing a step-by-step guide to qualitative data analysis through a critical realist lens. This paper offers learning for academics, researchers, and policymakers interested in engaging children and young people with disabilities in qualitative research.
PUBLISHED
https://doi.org/10.1177/1609406925137018